Pengembangan Media Digital Interaktif Berbasis Kearifan Lokal Tarian Bujangganong untuk Meningkatkan Berpikir Kritis Siswa SD - Yanita Andam Sari; Barokah Isdaryanti; Decky Avrilianda; Nuni Widiarti; Sari, Yanita Andam (Universitas Muhammadiyah Magelang, 2026)
This study aims to investigate the effect of interactive digital media based on the local wisdom of the Bujangganong Dance on students’ critical thinking skills in learning the human movement system for sixth-grade elementary school students. The background of this study is the low level of students’ critical thinking skills and the limited use of interactive, contextual, and culture-based learning media in classroom practice. This research employed a Research and Development (R&D) approach using the ADDIE model proposed by Robert Maribe Branch. The study involved sixth-grade elementary school students. Data were collected through expert validation questionnaires, teacher and student response questionnaires, interviews, observations, and pretest-posttest critical thinking assessments. The results indicated that the developed media was highly valid, with an average score of 3.60 from material experts and 3.50 from media experts. Practicality results showed positive responses from teachers (95.00%) and students (92.38%), indicating a very practical category. Effectiveness analysis revealed an increase in the mean score from 60.00 (pretest) to 82.00 (posttest), with an N-gain score of 0.55 (moderate category). Furthermore, the paired sample t-test showed a significant difference (p < 0.05), confirming that the media significantly improved students’ critical thinking skills. In conclusion, the interactive digital media based on local wisdom is valid, practical, and effective in enhancing students’ critical thinking skills in science learning on the human movement system topic.